Rubber seed clones identification using LDR module combined with Arduino: article - Adzmi, Muhammad Azuan Shah (2013)
The rubber seed clones identification are presented using LDR sensor and Arduino as a controller. The main objective of this project is to create an intelligent and simple identification of rubber seed that can recognize the clones based on colour being reflected by LDR module sensor. Rubber seed clones has different textures and colour characteristic though observation. The functions of this project are to select the best rubber tree series by using light dependent resistor (LDR) for analyze the intensity of light being reflected through a surface rubber seed. These projects need to identify five types of rubber seed clones. There are RRIM 2009, RRIM 2016, RRIM 2008, RRIM 2011 and RRIM 2005. The three of LDR module sensor are used and located at different distance to take the sample of reading. The device measure the percentages of reflectance based on the intensity of light reflected from the rubber seed surface. The output voltage measurement is then analyzed using recommended statistical test to identify the type of rubber seed. The Microsoft Office Excel was used to analysis the average voltage that convert from light reflect by takes 30 sample readings from 5 difference clones. The analyses are show in TABLE and graph and decided to take the average range as a conclusion to compare the type of every clone.